Students’ Speaking Skill in English Immersion School - Mohammad Fadil; Sumardi Sumardi; Ngadiso Ngadiso (Pancaran Pendidikan, 2018)
This research aims to describe: (1) students' English speaking skill in English immersion school; (2) students’ strengths and weaknesses in speaking skill in English immersion school; (3) factors affecting students' speaking skill in English immersion school. The research was designed as a case study, conducted at a school applying English immersion in Bondowoso, East Java, Indonesia in Academic Year 2017-2018. The research used purposive sampling. Data were collecated by interview, questionnairre, observation, and document analysis. The informants were grade 2 students, English teachers, and the school founder. The analysis found that: (1) on the scale of 1-5 (1=very bad, 2=bad, 3=fair, 4=good, 5=very good), students’ English speaking skills were at levels of very good (2.22%), good (6.67%), fair (37.78%), bad (44.44%), and very bad (8.89%); (2) students’ strengths in English speaking skills were related to vocabulary with average score of 2.7, and the weaknesses dealt with fluency with average score of 2.25; (3) factors that were assumed to affect students’ English speaking skills were environment, local accent, vocabulary mastery, English use, preference, and habits. It is recommended that all parties involved in the English immersion program evaluate the running of the program and the content of the program to provide learning outputs through English immersion. Commitment to using English should be strengthened, especially in English Week program. Improvement on English teachers’ is needed by involving them in trainings. Finally, similar research at non-English immersion school is necessary to ensure the comparative results gained from both types of school.